Australian Contributions to Strategic and Military Geography (Advances in Military Geosciences,, 2018)
Drawing from military geography's spatial roots, its embrace of dynamic systems, and integration of human and biophysical environments, this book helps in understanding the value of analyzing patterns, processes and systems, and cross-scale and multi-disciplinary ways of acting in a complex world, while making the case for a resurgence of strategic and military geography in Australia. Here, leading experts demonstrate that geography retains its relevance in clarifying the scale and dynamics of defense activities in assessments of the international, regional, national, and site impacts of changes in physical, cyber and human geographies. The cases presented show Australia contributing to a growing strategic and military geography. Contemporary publication in an important and emerging topic at a key time; Includes material from leading thinkers and practitioners in the field and crossing the academic-professional- practitioner interface; First synthesis of a post-modern strategic military geography and a forward-looking volume that includes human, biophysical and epistemological materials.